Using the Socio-Ecological Model to Frame Agricultural Safety and Health Interventions. Issue 4 (2nd October 2017) - Lee, Barbara C.; Bendixsen, Casper; Liebman, Amy K.; Gallagher, Susan S.
ABSTRACT: The Socio-Ecological Model (SEM) is a conceptual framework depicting spheres of influence over human behavior that has been applied in public health settings for nearly five decades. Core principles of all variations of the SEM are the multiple influences over an individual's behaviors, the interactions of those influences, and the multilevel approaches that can be applied to interventions intended to modify behaviors. A project team modified the standard SEM to address interventions for protecting children from agricultural disease and injury. The modified SEM placed the "child in the farm environment" at the core with five interrelated levels (spheres) of influence over the child. This framework provides guidance on how a multifaceted, multilevel intervention can maximize the potential for impact on behaviors and decisions made by parents/adults responsible for the safety of children on farms. An example of how this model could work to safeguard youth operating tractors is provided.